A Multilevel Empowerment Approach to Prevent Relapse and Improve Quality of Life of People with Mental Disorders - Agustin Widyowati; Bhisma Murti; Aris Sudiyanto; Suminah (Institute of Medico-legal Publications Pvt Ltd, 2021)
The global health problem that increases significantly every year is psychiatric disorders. Decrease in thequality of life of people with mental disorders, error in the recurrence rate suffered. This study aims to seethe effectiveness of holistic family-centered mental health care in preventing recurrence and improving thequality of life of people with mental disorders in Kediri Regency, East Java Province. The research designused RCT (Randomized Control Trial). The population in the study was people with mental disorders. Theresearch sample consisted of 38 groups of respondents and 38 control groups with the multistage randomsampling technique. Dependent variables were disease recurrence and quality of life for people with mentaldisorders. Va¬riabel independent is a family-centered holistic mental health care. The instrument uses aquestionnaire that has been tested for validity and reliability. Data analysis used an independent t-test usingSTATA 13. The t-test results showed that the increase in the average increase in the treatment group afterbeing given the intervention “family-centered holistic mental health care” while the control group did notchange significantly. Holistic, family-centered mental health care with a multilevel approach in this study iseffective in preventing relapses and improving the lives of people with mental disorders. It is hoped that itcan be used to help improve the quality of life for a wider range of people with mental disorders